A core outcome set for pre‐eclampsia research: an international consensus development study. (21st June 2020) - Duffy, JMN; Cairns, AE; Richards‐Doran, D; van 't Hooft, J; Gale, C; Brown, M; Chappell, LC; Grobman, WA; Fitzpatrick, R; Karumanchi, SA; Khalil, A; Lucas, DN; et al.
Abstract : Objective: To develop a core outcome set for pre‐eclampsia. Design: Consensus development study. Setting: International. Population: Two hundred and eight‐one healthcare professionals, 41 researchers and 110 patients, representing 56 countries, participated. Methods: Modified Delphi method and Modified Nominal Group Technique. Results: A long‐list of 116 potential core outcomes was developed by combining the outcomes reported in 79 pre‐eclampsia trials with those derived from thematic analysis of 30 in‐depth interviews of women with lived experience of pre‐eclampsia. Forty‐seven consensus outcomes were identified from the Delphi process following which 14 maternal and eight offspring core outcomes were agreed at the consensus development meeting. Maternal core outcomes: death, eclampsia, stroke, cortical blindness, retinal detachment, pulmonary oedema, acute kidney injury, liver haematoma or rupture, abruption, postpartum haemorrhage, raised liver enzymes, low platelets, admission to intensive care required, and intubation and ventilation. Offspring core outcomes: stillbirth, gestational age at delivery, birthweight, small‐for‐gestational‐age, neonatal mortality, seizures, admission to neonatal unit required and respiratory support. Conclusions: The core outcome set for pre‐eclampsia should underpin future randomised trials and systematic reviews. Such implementation should ensure that future research holds the necessary reach and relevance to inform clinical practice, enhance women's care and improve the outcomes of pregnant women and their babies. Tweetable abstract: 281 healthcare professionals, 41 researchers and 110 women have developed #preeclampsia core outcomes @HOPEoutcomes @jamesmnduffy. [Correction added on 29 June 2020, after first online publication: the order has been corrected.] Tweetable abstract: 281 healthcare professionals, 41 researchers and 110 women have developed #preeclampsia core outcomes @HOPEoutcomes @jamesmnduffy. [Correction added on 29 June 2020, after first online publication: the order has been corrected.] This article includes Author Insights, a video abstract available at https://vimeo.com/rcog/authorinsights16319